Health in the 2018 Italian general election. (13th November 2019) - Guicciardi, S; Quargnolo, M; Moser, G; D'Avenia, R; Toth, F; Pia Fantini, M
Abstract: Background: General elections represent a peculiar moment in which clear positions on relevant topics are more likely to emerge. Therefore, they may serve as a reference point to monitor policy development and to verify decision makers' accountability. The aim of this study is to systematically examine the proposals on health issues in the manifestos of the 38 parties running in the 2018 Italian general election, comparing them with the contents shared on social media. Methods: All the electoral manifestos published on the websites of each party and of the Italian Ministry of the Interior were collected and independently assessed by four evaluators. A list of 48 health themes grouped into 13 main domains into was then consensually created and used to classify the reported proposals. Parties' official social media accounts (Facebook and Twitter) were subsequently screened for selected keywords to determine the frequency and the content of health-related posts. Results: Thirty out of 38 parties included a specific section on health in their programmes or generally addressed healthcare topics. The most covered themes were health promotion and lifestyles, self-sufficiency of fragile populations, management of private healthcare and health workforce, although implementation strategies varied greatly and only in a few cases it was possible to compare them. On social media, health related posts represented less than 1% of the contents shared by any party during the election campaign. Conclusions: In the 2018 Italian election campaign the majority of the parties' manifestos explicitly addressed health issues but, apart from a few exceptions, significant differences were present in the themes and in the proposed solutions, mostly generic. On social media health was almost neglected. Despite its social relevance, health played a marginal role in the 2018 Italian election campaign.